Influence Capital Structure, Policy Dividends, Profitability and Tax Avoidance on Intrinsic Firm Value - Alfian, Chandra Bagas; Ghozali, Imam (International Journal of Economics Development Research (IJEDR), 2023)
This study examines the effect of capital structure, dividend policy, profitability, and tax avoidance on intrinsic firm value in manufacturing companies. This study used purposive sampling and used secondary data from financial statements. The data were processed with a multiple linear regression analysis test method. Structured capital significantly and negatively affects intrinsic firm value, indicating that the company depends on debt with a high level of debt burden. Profitability is proven to be a predictor in shaping the intrinsic firm value, with the results having a significant effect on intrinsic firm value. Dividend policy and tax avoidance have no effect on intrinsic firm value. The intrinsic firm value must be managed by management because it is a factor that investors pay attention to so the company should manage the resources, assets, and capital to gain profits. The need for optimization and efficiency of the use of debt in the company’s operations. The research findings indicate the need to improve corporate governance and minimize risks related to tax avoidance and dividend policy.This study adds an analysis of the effect of tax avoidance to find an explanation of whether tax avoidance is seen as an effort to carry out tax planning or as a non-compliance and its impact on the intrinsic firm value.